The Development of Al-Ashri Book to Improve Arabic Vocabulary Mastery for 7th Grade: Pengembangan Buku Al-Ashri untuk - Ridha Aulia; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2021)
This article aims to developing a crossword-based Al-'Ashri textbook in grade VII and to determine the improvement of the textbook on Arabic vocabulary mastery for grade VII at SMP Muhammadiyah 5 Tulangan. This study uses research and development (Research and development) with the Sugiyono development model. Data were collected through observation, interviews, documentation and tests. The results of this study indicate that the development of the crossword-based Al-'Ashri textbook based on the assessments of content experts and design experts obtained very feasible criteria. From the expert's assessment, a trial was conducted on seventh grade students at SMP Muhammadiyah 5 Tulangan and the development was able to improve the Arabic vocabulary mastery of the seventh grade students. This is evidenced by the results of the t-test analysis where tcount 10.82 > ttable 1.803 that means H1 is accepted.